2009
DOI: 10.3844/ajebasp.2009.122.132
|View full text |Cite
|
Sign up to set email alerts
|

Push Vs Pull: Factors Influence Student Retention

Abstract: Problem statement: Student retention becomes one of the most significant issues that administrators of colleges and universities must deal with in today’s highly competitive market. Approach: In fact retaining a student is fundamental to the ability of an institution to carry out its mission. A high rate of attrition is not only a fiscal problem for schools, but a symbolic failure of an institution to achieve its purpose. Results: There are many ways to keep students retain at the same col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 12 publications
0
12
0
Order By: Relevance
“…Declining student enrollment, decreased state and federal funding, and competition for students with other institutions, paired with increased pressure on college presidents from parents, students, and faculty to provide programs to ensure academic success, has lead to an increase in student support services (Leone & Tian, 2009). A study by Thomas (2002) reported that university support services, such as peer tutoring, are one of the main factors in student retention.…”
Section: Administrative Issues In Higher Educationmentioning
confidence: 99%
See 2 more Smart Citations
“…Declining student enrollment, decreased state and federal funding, and competition for students with other institutions, paired with increased pressure on college presidents from parents, students, and faculty to provide programs to ensure academic success, has lead to an increase in student support services (Leone & Tian, 2009). A study by Thomas (2002) reported that university support services, such as peer tutoring, are one of the main factors in student retention.…”
Section: Administrative Issues In Higher Educationmentioning
confidence: 99%
“…Bushong (2009) reported in The Chronicle of Higher Education that retention rates are down in all institutions except two-year colleges. Pressure from college presidents to increase retention and grade point averages (GPAs) has caused retention in higher education to become one of the most significant issues that college administrators must deal with in today's competitive market (Lau, 2003;Leone & Tian, 2009) and has called for an increase in student support services (Adams, 2011) and the centralization of programs (Pina, 2008b). "In fact retaining a student is fundamental to the ability of an institution to carry out its mission.…”
Section: Administrative Issues In Higher Educationmentioning
confidence: 99%
See 1 more Smart Citation
“…When institutions are not able to retain and graduate students, the consequences are two-fold. Lower retention rates have been shown to negatively impact the institutions reputation and financials (Leone & Tian, 2009). …”
Section: Effects Of Academic Unpreparednessmentioning
confidence: 99%
“…Due to decreases in student enrollment and state and federal funding, increased competition between institutions for student enrollment, along with the pressure from college administrators, faculty, and students to ensure academic success, many institutions have turned to offering a variety of tutoring services (Leone & Tian, 2009). …”
Section: Tutoring As An Academic Support Strategymentioning
confidence: 99%